10 Jahre archäogenetische Forschungen zur Domestikation des Pferdes. Die Arbeiten der Jahre bis 2018 - Benecke, Norbert (e-Forschungsberichte des DAI, 2018)
The article presents an overview of 10 years of archaeogenetic research on the domestication of the horse. The large variety of mtDNA lines in recent horses is largely due to the variability of the once domesticated wild populations. Typical coloring patterns of domestic horses appear around 3000 BC. In the transition to the Middle Ages, there is a significant decline in spotted and diluted color phenotypes. In Scythian horse breeding, selection for size and constitution of horses as well as physiological characteristics such as speed and endurance can be demonstrated. The diversity on the Y chromosome was initially high, but gradually decreased over time. After 400 AD, only one haplotype is detectable, as in the case of recent horses. Ambling gaits (pace, tölt) appear for the first time in Western Europe in the early Middle Ages.